Transformation of the fortifications located north of the Camino Real de Tierra Adentro in Mexico: The case of El Pasaje Prison - CARRILLO ACOSTA, ROBERTO (2018)
Investigations about the fortifications of northern New Spain are scarce. Besides, even though there are isolated writings on some types of fortification, no studies have been carried out that comprehensively track each fortified enclosure. The Camino Real de Tierra Adentro, the reason for this article, has left us an immense testimony of various historical processes forged in it. This testimony translates into a range of patrimonial assets that were built individually and collectively over the course of three centuries. Its transformation gives an account of the inherited knowledge of techniques or constructive models, and of the occupation strategies, which impress on it a sense of permanence in time.